Central arterial and peripheral arterial blood pressure in patients with chronic kidney disease undergoing versus not undergoing hemodialysis. Issue 4 (October 2020) - Sun, Liping; Zhou, Ru; Zhang, Xinzhou
Objective: We assessed the consistency of noninvasive and invasive measurements of central arterial pressure (CAP) and the difference between peripheral brachial artery pressure and CAP in patients with chronic kidney disease (CKD) undergoing versus not undergoing hemodialysis. Methods: This single-center cross-sectional study was performed from May to December 2018. The patients were divided into a control group (n = 50), CKD group (stages 3–5, n = 50), and dialysis group (n = 20), and all underwent measurement of peripheral humeral arterial pressure and noninvasive and invasive measurement of CAP. Group differences and correlations between CAP and peripheral arterial pressure were assessed. Results: The consistency between noninvasive and invasive CAP was better in the control and CKD groups than in the dialysis group. In the dialysis group, the noninvasive equipment underestimated the actual CAP. The CAP was close to the peripheral brachial artery pressure in the dialysis group, while the CAP was significantly lower than the peripheral brachial artery pressure in the control and CKD groups. Conclusion: Noninvasive equipment underestimates the actual CAP in patients undergoing dialysis and should be used with caution. The difference between the peripheral arterial pressure and CAP was smaller in patients undergoing dialysis than in patients with CKD and controls.